Differential ligand binding to a human cytomegalovirus chemokine receptor determines cell type-specific motility. - Jennifer Vomaske; Ryan M Melnychuk; Patricia P Smith; Joshua Powell; Laurel Hall; Victor DeFilippis; Klaus Früh; Martine Smit; David D Schlaepfer; Jay A Nelson; Daniel N Streblow (PLoS Pathogens)
While most chemokine receptors fail to cross the chemokine class boundary with respect to the ligands that they bind, the human cytomegalovirus (HCMV)-encoded chemokine receptor US28 binds multiple CC-chemokines and the CX(3)C-chemokine Fractalkine. US28 binding to CC-chemokines is both necessary and sufficient to induce vascular smooth muscle cell (SMC) migration in response to HCMV infection. However, the function of Fractalkine binding to US28 is unknown. In this report, we demonstrate that Fractalkine binding to US28 not only induces migration of macrophages but also acts to inhibit RANTES-mediated SMC migration. Similarly, RANTES inhibits Fractalkine-mediated US28 migration in macrophages. While US28 binding of both RANTES and Fractalkine activate FAK and ERK-1/2, RANTES signals through Galpha12 and Fractalkine through Galphaq. These findings represent the first example of differential chemotactic signaling via a multiple chemokine family binding receptor that results in migration of two different cell types. Additionally, the demonstration that US28-mediated chemotaxis is both ligand-specific and cell type-specific has important implications in the role of US28 in HCMV pathogenesis.